WORKSHOP OPTIMALISASI KAPABILITAS SOSIAL PETANI DALAM MITIGAS BENCANA PANGAN DI DESA MATANG DANAU KABUPATEN SAMBAS - Herlan, Herlan; Rupita, Rupita; Marini, Marini; Efriani, Efriani (Jurnal Abdi Insani, 2025)
This Community Service Activity (PKM) was carried out in the form of a workshop with the theme of Optimizing Farmers' Social Capabilities in Food Disaster Mitigation in Matang Danau Village, Sambas Regency. The background of this activity stems from Indonesia's condition as an agrarian country that still relies on agriculture, especially rice, as the backbone of food supply. Although national rice production in January–June 2025 increased significantly to 19.16 million tons, food security still faces major challenges due to climate change, crop failures, and food distribution inequalities. The purpose of this activity was to increase farmers' understanding of the concepts of national and family food security, as well as to identify and optimize their social capabilities for food disaster mitigation. The workshop was held on August 23, 2025, and was attended by 30 participants consisting of farmers. The methods used included a pre-test, material delivery, group discussions, social capability mapping, and a post-test to measure the increase in participants' knowledge. The evaluation results showed an average score increase from 52 on the pre-test to 82 on the post-test, or an increase of 30 points (57.7%). In addition, participants successfully identified four main pillars of social capabilities in Matang Danau Village, namely social capital, local knowledge, social institutions, and social solidarity. Group discussions revealed various practices such as mutual cooperation in repairing irrigation systems, rice barns, the use of terajoong, and the tradition of sharing grain during crises. In conclusion, this workshop succeeded in increasing participants' understanding and awareness that social capabilities are an important force that can be mobilized to deal with the risk of food crises. Recommended follow-up actions include the establishment of a Resilient Food Farmers Forum, the revitalization of village granaries, the strengthening of the role of youth and women, and ongoing assistance from the government and universities. Keywords: food security, social capabilities, farmers, disaster mitigation, Matang Danau Village